The Influence of Ownership Concentration on Firm Resource Allocations to Employee Relations, External Social Actions, and Environmental Action - Crisóstomo, Vicente Lima; Freire, Fátima de Souza (Review of Business Management, 2015)
Objective – The purpose of this work is to examine the influence of ownership concentration on the funds allocated to CSR in Brazilian firm. Design/methodology/approach – Econometric models have been estimated, with an index of CSR as the dependent variable, and ownership concentration as the explanatory variable, together with relevant control variables suggested in the literature (profitability, leverage, growth opportunities, and firm size). A Brazilian CSR database has been built using data extracted from two different sources, one relative to CSR data and another that provides ownership structure and financial data. CSR policy is proxied by an index obtained as the ratio between funds directed to social action (employee relations, external social actions, and environmental action) and net sales. Findings – The findings indicate that CSR is positively influenced by firm ownership concentration in Brazil. Practical implications – The positive influence of ownership concentration on CSR may be an indication that large controlling shareholders of Brazilian firm may be considering CSR as an effective way to improve the image and reputation of the firm and its owners. This belief may be stimulating CSR projects and their disclosure in Brazil. Originality/value – This work is an additional contribution to the debate about the role played by ownership structure on CSR. Taking into account that the central point of Stakeholder Theory is a firm’s concern with all its stakeholders, the research builds on Stakeholder and Agency Theories by assessing the influence of large controlling shareholders on a firm’s social concerns.